Técnicas de optimización para la asignación de frecuencias en redes móviles de quinta generación - Alava Lara, Darley Steven (2024)
The fifth generation of mobile networks (5G) aims to revolutionize connectivity by offering unprecedented data transmission speeds, low latency, and massive network capacity. However, 5G's broader and more diverse frequency spectrum presents unique challenges, particularly in efficiently assigning frequencies to users to maximize network performance and user satisfaction. This research focuses on identifying the most effective optimization technique for frequency allocation in 5G mobile networks. With the wide range of frequency bands available in 5G, efficiently assigning these frequencies has become crucial for maximizing network performance and enhancing user experience. This study examines how different techniques, such as carrier aggregation and scheduling algorithms like Round Robin, Proportional Fair, and MAXCI, impact frequency distribution and allocation in densely populated environments. Strategies for contiguous and non-contiguous carrier aggregation are explored to assess their effectiveness in utilizing fragmented spectrum to deliver high-speed services. Through detailed simulations, the study aims to determine the most promising methodology for efficient frequency allocation, considering the unique complexity and dynamics of 5G networks. This analysis will contribute to a better understanding of how to optimize frequency allocation to support the increasing data demand and service diversity in the 5G era.